Experience of Surgical Treatment of Tuberculous and Nonspecific Spondylitis with a Barrier Collagen Membrane to Stimulate Osteogenesis in the Site of Bone Block Formation - E. O. Peretsmanas; A. A. Bezzubov; N. N. Nikolaev; V. A. Chumakov; I. V. Golubenkov (Туберкулез и болезни лёгких)
The objective: to increase effectiveness of surgical treatment of infectious spondylitis with impaired support function of the spinal column through the combined use of a titanium cylindrical block mesh, a resorbable double-sided collagen membrane and an osteoconductor to achieve successful spinal fusion.Subjects and Methods. A prospective monocenter cohort study included 17 patients with infectious spondylitis who were operated with anterior spinal fusion with a titanium mesh graft filled with an osteoconductor and delimited by a barrier double-sided collagen membrane. In the postoperative period, antibacterial treatment was administered based according to the results of bacteriological tests of biological specimensl. Formation of the bone block (spondylodesis) was evaluated by the scale for assessing the fusion of the graft with the bed of the cranial and caudal vertebrae.Results. 6 months after surgery, the fusion of the graft with the bed of the supporting vertebra according to the Baulin scale was 4.5 ± 0.4 scores on the average. In 5 (29%) patients, a clear, homogeneous bone block with a transition of bone beams was achieved after surgery which amounted to 5 scores by the Baulin scale.